TiO2-pillared clays with well-ordered porous structure and excellent photocatalytic activity1. Issue 11 (7th February 2015) - Yang, Jae-Hun; Piao, Huiyan; Vinu, Ajayan; Elzatahry, Ahmed A.; Paek, Seung-Min; Choy, Jin-Ho
<x xml:space="preserve">Abstract</x> TiO2-pillared clays with well-ordered porous structures are successfully prepared via incorporating TiO2 nanosol particles into the clays, where empty octahedral sites are partially modified with divalent metal ions such as Mg2+ and Fe2+.